1996
DOI: 10.1007/s002770050179
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to factor VIII in plasma of patients with hemophilia A and normal subjects

Abstract: Non-neutralizing factor VIII (FVIII) antibodies (FVIII-Ab) in hemophilia A may be associated with an abnormal clinical response to FVIII concentrates. Patients with FVIII inhibitors may develop noncoagulation FVIII-Ab after the induction of immunotolerance. Natural FVIII-Ab may be detected in the plasma of some healthy subjects. The aim of this study was to analyze the presence of FVIII-Ab in the plasma of 53 normal blood donors and 124 patients with hemophilia A (18 patients had a previous history of FVIII in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 24 publications
2
43
1
3
Order By: Relevance
“…The incidence of autoantibodies in the healthy population examined by our assay is at the low end of reported frequency (0%-36%) for healthy individuals. [41][42][43][44][45][46] The high incidence of antibodies in healthy donors reported by others might arise due to the lack of nonspecific binding controls in the detection assays used to analyze the samples. Inclusion of a binding control in our assay largely eliminates from analyses signals from the nonspecific binding of plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of autoantibodies in the healthy population examined by our assay is at the low end of reported frequency (0%-36%) for healthy individuals. [41][42][43][44][45][46] The high incidence of antibodies in healthy donors reported by others might arise due to the lack of nonspecific binding controls in the detection assays used to analyze the samples. Inclusion of a binding control in our assay largely eliminates from analyses signals from the nonspecific binding of plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This rate of ADA development is in line with other recently approved rFVIII products, 7 and the incidence of non-neutralizing antibodies against FVIII in healthy individuals and in patients with hemophilia. 22,23 Eight patients had non-inhibitory ADAs prior to dosing with rVIII-SingleChain, 7 of whom remained ADA positive at the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, NNA prevalence ranged from 2% to 3% in healthy individuals 16,18,21,24 and from 12.2% to 53.8% in patients with hemophilia A. [13][14][15][16][17][18][19][20][21][22]24,25,29,30 Several factors, particularly that all previous studies predominantly included patients with multiple transfusions, explain this large variation and the gaps in knowledge about their potential clinical role.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22]24,25,29,30 Several factors, particularly that all previous studies predominantly included patients with multiple transfusions, explain this large variation and the gaps in knowledge about their potential clinical role. For instance, the intron 22 inversion of FVIII mutation was associated with an increased frequency of NNAs in patients who had had multiple transfusions in 1 study 29 that was not confirmed in another study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation